Numerical Study for the Tube Rotation Effect on Melting Process in Shell and Tube Latent Heat Energy Storage LHES System (Journal of Engineering, 2021)
Although renewable energy systems have become an interesting global issue, it is not continuous either daily or seasonally. Latent heat energy storage (LHES) is one of the suitable solutions for this problem. LHES becomes a basic element in renewable energy systems. LHES compensate for the energy lack when these systems are at low production conditions. The present work considered a shell and tube LHES for numerical investigation of the tube rotation influence on the melting process. The simulation and calculations were carried out using ANSYS Fluent software. Paraffin wax represents the phase change material (PCM) in this work, while water was selected to be the heat transfer fluid (HTF). The calculations were carried out for 9 rpm tube rotation case as well as the stationary case. The results show a slight increase in the liquid content of phase change material PCM due to tube rotation. The enhancement percentage in liquid content was 3.5% for 6 hrs charging process. The heat transfer in the axial direction was small relative to that in the radial direction.